Beyond elections rituals - Rethinking public participation in Kenya's public finance management - Wanjiku, Francis Njoroge (Strathmore University, 2018)
Public participation is one of the edicts of the Constitution of Kenya, 2010 which aims to promote transparency and accountability of public resources to the people of Kenya. One of the principles of public finance in Kenya is to promote transparency and accountability in the process of public finance. This paper seeks to find out ways in which different levels of government have breathed new life into this principle of good governance. Before the enactment of the Constitution of Kenya, 2010 Kenya did not have any kind of legislative statute that promoted transparency in the public finance system; it was done at the whim of the executive. Budget statements would be read at the request of the President; finance bills would be legislated in Parliament at any period during a financial year, parliament would rubber stamp budget statements without scrutiny and most importantly the people of Kenya were not involved in the process-apart from watching the Minister for Treasury annually posing with the popular briefcase engraved with the court of arms and thereafter reading the budget statement live on state television. This events allowed the researcher to explore what really is public participation. Public participation is the process by which government consults with interested or affected individuals, organizations, and other necessary stakeholders before making a decision. Other terms sometimes used are “public involvement,” “community involvement,” or “stakeholder involvement. The study has gone further to identify important principles that should be adhered to in order to build a successful model of public participation. In conclusion, the study proposes a two way communication system which allows deliberation rather than mere participation. In order to strengthen the democratic principles upon which the country is founded upon, the executive and legislature must go beyond legislative intent and allow the people’s contribution to influence public debate and policies. It cannot be that public finance matters are left to the few technocrats at the Ministry of Treasury and Parliament.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School
Keywords: Public participation; Election rituals; Finance management_Kenya